Making the Strange Familiar. (6th September 2015) - Pike, Sarah
Abstract : From studying Pagan festivals as a graduate student to writing about Burning Man, Hare Krishna hardcore music, ecstatic dance and so-called eco-terrorists twenty years later, this essay describes my journey as an academic through what many other religious studies scholars might consider the fringe of our academic purview. In the essay I consider the ways in which the concerns that emerged in my earliest work in Pagan Studies—sacred space, the role of memory in identity construction, relationships with the more-than-human world, ritual creativity, religious freedom, childhood experience and religious improvisation—continue to be central to my scholarship over two decades later.